2018
DOI: 10.1111/desc.12775
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a sensitive period in the effects of early life stress on hippocampal volume

Abstract: Exposure to stress has been causally linked to changes in hippocampal volume (HV). Given that the hippocampus undergoes rapid changes in the first years of life, stressful experiences during this period may be particularly important in understanding individual differences in the development of the hippocampus. One hundred seventy‐eight early adolescents (ages 9–13 years; 43% male) were interviewed regarding exposure to and age of onset of experiences of stress; the severity of each stressful event was rated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 69 publications
5
56
1
2
Order By: Relevance
“…First, animal studies already showed that factors altering early postnatal hippocampal neurogenesis are essential in schizophrenia-like symptoms progression as a whole 48 . Second, human studies have shown that early-life insults before 5 years, but not later in childhood, can be responsible for the association between stress severity and reduced hippocampal volumes 49 . Interestingly, childhood trauma has regularly been reported to be associated with the severity of AH in psychosis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First, animal studies already showed that factors altering early postnatal hippocampal neurogenesis are essential in schizophrenia-like symptoms progression as a whole 48 . Second, human studies have shown that early-life insults before 5 years, but not later in childhood, can be responsible for the association between stress severity and reduced hippocampal volumes 49 . Interestingly, childhood trauma has regularly been reported to be associated with the severity of AH in psychosis (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…More work is needed investigating if there are sensitive periods in development when maltreatment has more robust consequences on neurobiology. Humphreys et al (2019) recently reported hippocampal volume differences were associated with stress severity during early childhood (≤5 years of age) but there was no association between hippocampal volumes and stress occurring during later childhood [226]. Studies investigating interactions between childhood maltreatment and genetic variation/familial risk for mood disorders could identify mechanisms underlying risk and resiliency in the absence of some study related confounds (i.e.…”
Section: Limitations/future Directionsmentioning
confidence: 99%
“…For example, in rats subjected to contextual fear conditioning, ELS causes synaptic inhibition between the hippocampus and the medial prefrontal cortex in response to the extinction trials, and this is accompanied by persistent freezing due to impaired extinction retrieval of the fear memory (Judo et al, 2010), a feature of PTSD in humans (Maren et al, 2013;Garfinkel et al, 2014). Decreased hippocampal volume as a result of ELS has been reported in both animal and human models (Uno et al, 1994;Andersen and Teicher, 2004;Humphreys et al, 2019) and this is consistent with significant hippocampal volume reductions in combat-and childhood-related PTSD (Bremner et al, 1995(Bremner et al, , 1997Karl et al, 2006;Wang et al, 2010) that worsens over the duration of the disorder (Felmingham et al, 2009;Chao et al, 2014). These findings are not confined to PTSD; reduced hippocampal function has also been identified as a feature of AD (Agartz et al, 1999;Beresford et al, 2006), cannabis dependence (Chye et al, 2019), and methamphetamine psychosis (Orikabe et al, 2011).…”
Section: Early Life Stressmentioning
confidence: 99%